Equivalent support stiffness approach to free vibration response of cooling towers - Kulkarni, Sachin R.; Hosur, Vinod (Journal of Structural Engineering, 2024)
Modelling of support boundary condition of the shell as built in or pinned for the evaluation of the free vibration response of cooling tower shell is unrealistic. The modelling of column support and foundation with underlying soil though rigorous, requires large computational time and effort. Therefore it is proposed to evolve a simplified model to replace both column supports and the foundation on soil by equivalent support stiffness at the base of the shell as support boundary condition. The validation and effectiveness of the proposed equivalent support stiffness as support boundary condition for the tower is demonstrated by a numerical example. The sensitivity of the support boundary conditions on the free vibration response of the cooling towers is evaluated. The natural frequencies of lower modes are found to be more sensitive to the support stiffness compared to the higher modes.